Un référendum sur l’indépendance est-il possible dans l’ordre juridique espagnol ? Le droit expliqué dans la presse - Jorge Cagiao y Conde (Cahiers de Civilisation Espagnole Contemporaine)
Since the end of 2012, an intense debate over the possibility of Catalonia’s independence and the legal channels to call an independence referendum has been taking place. Newspapers provide constitutional law experts with a privileged space to explain to citizens the way in which the Catalan referendum problem could be legally solved. This article analyzes the arguments offered by some of the most influential constitutional law scholars and tries to show that, far from adopting a scientific approach, the ideological approach prevails in many of their works.